MITIGASI BENCANA TANAH LONGSOR DI DESA TANAH ABANG UTARA KECAMATAN TANAH ABANG KABUPATEN PALI - Ahmad Hidayat; Bhakti Yudho Suprapto; Desmarita Desmarita (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2025)
Landslides are natural disasters caused by slope instability resulting from geomorphological, hydrological, and human activity factors. This phenomenon can occur suddenly or gradually, causing significant impacts on infrastructure, safety, and community access. In North Tanah Abang Village, Tanah Abang District, PALI Regency, the landslide risk is quite high due to steep topography, erosion of the Lematang River, and human activities such as deforestation and sand mining. Risk analysis through parameters such as geology, topography, rainfall, and land use indicates a moderate to high danger level in this area. Effective mitigation efforts include structural approaches like terracing and retaining walls, as well as non-structural approaches such as reforestation, community education, and land use regulation. The implementation of early warning systems is also a crucial step in reducing the impacts and losses caused by landslides. Through these measures, it is expected that the landslide disaster risk in this region can be minimized and community preparedness improved.